Effects of continuous monoculture on rhizosphere soil nutrients, growth, physiological characteristics, hormone metabolome of Casuarina equisetifolia and their interaction analysis - Yuhua Wang; Yuchao Wang; Jianjuan Li; Yuhong Cai; Mingyue Hu; Wenxiong Lin; Zeyan Wu (Heliyon, 2024)
Continuous planting is unavoidable in agricultural production, but continuous planting affects plant growth and physiological characteristics. In this study, we analyzed rhizosphere soil nutrients, physiological characteristics, hormone metabolome changes and their interactions of Casuarina equisetifolia (C. equisetifolia) with the increase of continuous planting number. The results found that C. equisetifolia root was significantly inhibited, the plant height was dwarfed and the biomass was significantly reduced as continuous planting number increased. Secondly, continuous planting caused a decrease in the rhizosphere soil nutrient transformation capacity, and a significant decrease in the total soil nutrient and available nutrient content. Analysis of physiological indexes showed that continuous planting resulted in a decrease in nitrogen, phosphorus, and potassium content, a decrease in the activity of physiological indexes of resistance, and a decrease in photosynthetic capacity of C. equisetifolia leaves. Hormone metabolome analysis showed that continuous planting critically affected the accumulation of five characteristic hormones in C. equisetifolia leaves, in which salicylic acid 2-O-β-glucoside (SAG), 2-oxindole-3-acetic acid (OxIAA), trans-zeatin-O-glucoside (tZOG) and gibberellin A3 (GA3) content decreased significantly while abscisic acid (ABA) content increased significantly. In conclusion, continuous planting lowered the rhizosphere soil nutrient transformation capacity of C. equisetifolia, lowered the soil available nutrient content, inhibited their root growth, and hindered the nutrient uptake and transportation by the root, thus led to the decrease of the nutrient accumulation capacity in the leaves of C. equisetifolia, and the decrease of SAG, OxIAA, and tZOG, GA3 synthesis ability decreased, ABA accumulated in large quantities, C. equisetifolia resistance and photosynthesis ability decreased, and their growth was impeded. This study provides insights for the effective management of continuous planting in the cultivation of C. equisetifolia.